Expressão da Endopeptidase 24.15 nos órgãos linfóides - Oliveira, Cayo Riketh Medeiros de (Universidade Federal Rural do Semi-Árido, 2010)
EP24.15 (endopeptidase 24.15, EC.3.4.24.15) also know as thimet-oligopeptidase is a metal dependent peptidase involved in the metabolism of neuropeptides as well as MHC-I peptides and more recently important as regulator of protein/protein interactions. The aim of this work is to verify the tissue and cellular distribution of EP24.15 in the lymphoid tissues (thymus, spleen, lymph nods) by means of immunohistochemistry technique. The analysis revealed that EP24.15 is expressed throughout the studied organs, nevertheless the tissue distribuition showed some areas that contained several labeled cell and others devoid of labeling. The cytoplasmic labeling was more frequent if compared to nuclear one. Macrophage is the cell type more fequently labled. The results suggest that it can be involved in the MHC-I peptide metabolism as well as CTLs differentiation.
Ep24.15 distribution in lymphoid tissue
Keywords: endopeptidase 24.15, Macrophage; endopeptidase 24.15; macrófago e MHC classe I; CIENCIAS AGRARIAS::MEDICINA VETERINARIA